The architectonic of philosophy Plato, Aristotle, Leibniz - Kavanaugh, Leslie Jaye (Amsterdam University Press, 2007)
"Whereas the history of philosophy defines metaphysics as asking the question 'What is Being?'; here is asked 'Where is Being?' What is to be analyzed is indeed part of the tradition of metaphysics to inquire about Being qua being, but here the inquiry is into its structure, its position within the ontological whole. The concept of the 'architectonic' is borrowed from Kant ... In this work, three philosophical structures are chosen for a more extensive examination: the three 'architectonics' are that of Plato's Chora, Aristoteles' continuum, and finally Leibniz's labyrinth"--Back cover.